Hot-dip galvanized steel sheet and its manufacturing method
Patent Information
- Application Number
- JP2024534743
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-09-27
- Filing Date
- 2024-01-23
- Publication Date
- 2025-02-26
- Estimated Expiration
- 2044-01-23
AI Technical Summary
【0012】 本発明によれば、高強度を有し、不めっきのない美麗な表面外観を有するとともに、耐遅れ破壊特性に優れた溶融亜鉛系めっき鋼板およびその製造方法が提供される。
Smart Images

Figure 0007635892000001 
Figure 0007635892000002 
Figure 0007635892000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a hot-dip galvanized steel sheet and a method for producing the same. [Background technology]
[0002] In recent years, surface-treated steel sheets that have been given rust-resistance, particularly hot-dip galvanized steel sheets (including alloyed hot-dip galvanized steel sheets) with excellent rust-resistance, have been widely used in the fields of automobiles, home appliances, building materials, etc. From the viewpoint of improving fuel efficiency and collision safety of automobiles, the application of high-strength steel sheets to automobile body materials is progressing in order to reduce the thickness by increasing the strength of the automobile body materials and to make the automobile body itself lighter and stronger. In general, hot-dip galvanized steel sheets are produced by using hot-rolled or cold-rolled steel sheets as base materials, subjecting the base steel sheets to recrystallization annealing in the annealing furnace of a CGL, and then subjecting them to hot-dip galvanizing. On the other hand, alloyed hot-dip galvanized steel sheets are produced by further subjecting the hot-dip galvanizing to alloying treatment.
[0003] In annealing, the steel sheet needs to be held in a reducing atmosphere containing hydrogen. At this time, hydrogen in the furnace penetrates into the steel sheet, and the steel sheet is then subjected to a cooling treatment and a hot-dip plating treatment, so that hydrogen remains in the steel sheet as diffusible hydrogen in steel. Since hydrogen is not permeable through plating, the diffusible hydrogen in steel is not released from the steel sheet after plating, and there was a problem that the delayed fracture resistance property is reduced when the amount of diffusible hydrogen in steel is large. In particular, in high-strength steel sheets with a tensile strength of 780 MPa or more, the diffusible hydrogen in steel is likely to remain after annealing, and there was a problem that the delayed fracture resistance property is significantly reduced. This is because in high-strength steel sheets with a tensile strength of 780 MPa or more, in order to obtain a specified strength, it is necessary to form a hard structure such as martensite or bainite, and for this purpose, it is necessary to generate an austenite phase in the annealing process, but the austenite phase is more likely to absorb a large amount of hydrogen than the ferrite phase, and the diffusion rate of hydrogen is slow, so once hydrogen is absorbed in the annealing process, it is difficult to release it in the cooling process. In recent years, there has been a tendency for such standards for delayed fracture resistance to become stricter.
[0004] Conventionally, as steel sheets having a reduced amount of hydrogen therein, for example, the following have been proposed. Patent Document 1 discloses a high-strength galvannealed steel sheet that has excellent delayed fracture resistance and hole expandability, and in which the amount of hydrogen released when the steel sheet is heated to 200°C is 0.35 mass ppm or less. Patent Document 2 discloses a high-strength galvanized steel sheet that has excellent plating properties and bendability and that releases hydrogen in an amount of 0.25 mass ppm or less when the steel sheet is heated to 210°C. Patent Document 3 discloses a high-strength galvanized steel sheet that has excellent plating properties and bendability, and has a tensile strength of 1,100 MPa or more, and in which the amount of hydrogen released when the steel sheet is heated to 210°C is 0.25 mass ppm or less. Furthermore, as a technique for producing a steel sheet having a reduced amount of hydrogen therein, for example, the following has been proposed. Patent Document 4 discloses a technique in which a hot-rolled steel sheet is subjected to a reduction treatment, then dehydrogenation treatment at 450 to 550° C. in an atmosphere with a H2 concentration of 8 to 20%, and then hot-dip galvanization is performed. Patent Document 5 discloses a technique for reducing the amount of hydrogen in a hot-rolled steel sheet by controlling the relationship between the annealing temperature in an annealing furnace and the hydrogen concentration to satisfy the following formula (1) in a method of reducing a hot-rolled steel sheet at a temperature in the range of 650 to 950°C and then hot-dip galvanizing the steel sheet. 1≦H≦-0.05×RT+57.5 (1) Here, H is the hydrogen concentration in the furnace (%), and RT is the annealing temperature (°C).
[0005] Patent Document 6 discloses a technique for obtaining good surface quality in a method for performing hot-dip galvanizing after reduction annealing of a steel sheet containing Si, Mn, and Al, by controlling the hydrogen concentration in a furnace during reduction annealing to be 10% by volume or more, and the relationship between the hydrogen partial pressure and the water vapor partial pressure in the furnace atmosphere gas at 650°C or more and less than 750°C to satisfy the following formula (2), and similarly controlling the relationship between the hydrogen partial pressure and the water vapor partial pressure in the furnace atmosphere gas at 750°C or more and 950°C to satisfy the following formula (3). log(P H2O / P H2 )≦-1.55 (2) -0.91≦log(P H2O / P H2 )≦-0.635 (3) [Prior art documents] [Patent documents]
[0006] [Patent Document 1] International Publication No. 2019 / 189067 [Patent Document 2] International Publication No. 2019 / 189849 [Patent Document 3] International Publication No. 2019 / 189841 [Patent Document 4] Japanese Unexamined Patent Publication No. 54-130443 [Patent Document 5] Patent No. 3266008 [Patent Document 6] Patent No. 5811841 Summary of the Invention [Problem to be solved by the invention]
[0007] However, in the techniques shown in Patent Documents 1, 2, and 3, in order to meet the stricter standards for delayed fracture resistance, it is necessary to generate an austenite phase, particularly in the annealing process, but the delayed fracture resistance of high-strength steel sheets could not be sufficiently improved. Furthermore, the techniques shown in Patent Documents 4 and 5 are both intended to suppress blisters (plating bulges) in hot-rolled steel sheets, and in order to improve the delayed fracture resistance of high-strength steel sheets having an austenitic phase in the annealing process, it is necessary to further reduce the amount of hydrogen in the atmosphere to reduce hydrogen in the steel. However, if the amount of hydrogen in the atmosphere is further reduced, the selective oxidation of easily oxidizable elements such as Si and Mn contained in the high-strength steel sheet is promoted, which inhibits galvanization and makes it impossible to obtain good surface quality. Therefore, it is difficult to improve good surface quality and delayed fracture resistance with the method of uniformly reducing hydrogen in the furnace as described in Patent Documents 4 and 5. In addition, the technology shown in Patent Document 6 aims to improve the galvanic properties of steel containing Si, Mn, and Al and to obtain good surface quality by changing the ratio of water vapor partial pressure to hydrogen partial pressure according to the annealing temperature. However, it is necessary to control the hydrogen concentration in the furnace to 10% or more, and no consideration is given to reducing the hydrogen concentration contained in the steel, so that it is difficult to improve the delayed fracture resistance of high-strength steel sheets.
[0008] Therefore, an object of the present invention is to solve the above-mentioned problems of the conventional art and to provide a manufacturing method by which a hot-dip galvanized steel sheet having high strength, a beautiful surface appearance free of uncoated areas, and excellent delayed fracture resistance can be manufactured.
[0009] Here, high strength refers to a steel plate having a tensile strength TS of 780 MPa or more when a tensile test is performed in accordance with JIS Z2241 (2011). A beautiful surface appearance without any uncoated areas refers to the fact that the appearance of the plating on a hot-dip galvanized steel sheet is visually observed, and for those that show patterns or irregularities, SEM observation is carried out and there are less than three uncoated defects within an area of 1 m x 1 m of the steel sheet. Excellent resistance to delayed fracture properties means that a rectangular test piece with a major axis length of 100 mm and a minor axis length of 20 mm is taken from a steel plate, a punched hole with a diameter of 15 mm and a clearance of 14.0% is formed at the center of the major and minor axes of this test piece, and the piece is subjected to a tensile test (tensile speed 10 mm / min). The load time in the tensile test is up to 100 hours, and the maximum stress at which no cracks occur after 100 hours of load is defined as the limit stress, and the limit stress / yield stress is 1.00 or more. The clearance was previously set at around 12.5%, but due to the recent trend towards stricter quality standards regarding delayed fracture resistance, stricter conditions have been adopted compared to the past. [Means for solving the problem]
[0010] As a result of extensive investigations aimed at solving the above problems, the present inventors have newly revealed that hydrogen released when the temperature of a steel sheet is raised to less than 200°C is released into the atmosphere when the steel sheet is held after production, whereas hydrogen released when the temperature of a steel sheet is raised to between 200°C and 350°C (hereinafter referred to as quasi-diffusible hydrogen) is not released into the atmosphere when the steel sheet is held after production, and is transformed into diffusible hydrogen when the steel sheet is processed, particularly by press working, which significantly affects delayed fracture resistance. Furthermore, the present inventors have found that in a manufacturing method of a hot-dip galvanized steel sheet in which a steel sheet (base steel sheet) is annealed and cooled, and then hot-dip galvanized, a hot-dip galvanized steel sheet having excellent coating appearance and delayed fracture resistance can be manufactured by optimizing the atmosphere for annealing and cooling.
[0011] The present invention has been made based on these findings, and the gist of the present invention is as follows. [1] In mass percent, C: 0.06% or more and 0.30% or less, Si: 0.01% or more and less than 3.00% Mn: 1.5% or more and 3.5% or less, P: 0.1% or less (excluding 0%) S: 0.003% or less (excluding 0%) Sol.Al: 0.1% or less (excluding 0%) N: 0.007% or less (excluding 0%) O: Contains 0.003% or less (excluding 0%) A base steel plate having a composition with the balance being Fe and unavoidable impurities; The coating weight per side formed on the surface of the base steel sheet is 20 g / m 2 More than 120g / m 2 and a zinc-based plating layer, The base steel sheet has a total hydrogen release amount of 0.20 mass ppm or less at 200° C. or more and 350° C. or less when measured by temperature rise analysis, Within an area of 1m x 1m on the steel plate surface, there are less than three uncoated defects. Hot-dip galvanized steel sheet with a tensile strength of 780 MPa or more. [2] The hot-dip galvanized steel sheet according to [1], wherein the base steel sheet further contains, as the chemical composition, one or more groups selected from the following groups A to D, in mass %: Group A Nb: 0.05% or less (excluding 0%) Ti: 0.08% or less (excluding 0%) V: 0.2% or less (excluding 0%) W: 0.15% or less (excluding 0%) Zr: 0.15% or less (excluding 0%), one or more selected from the following Group B Cr: 1% or less (excluding 0%) Ni: 1% or less (excluding 0%) Cu: 1% or less (excluding 0%) Mo: 1% or less (excluding 0%) Co: 1% or less (excluding 0%) B: 0.005% or less (excluding 0%), one or more selected from the following Group C: Ca: 0.005% or less (excluding 0%) Mg: 0.005% or less (excluding 0%) REM: 0.005% or less (excluding 0%), one or more selected from the following Group D: Sn: 0.2% or less (excluding 0%) Sb: 0.2% or less (excluding 0%), one or more selected from the following [3] The hot-dip galvanized steel sheet according to [1] or [2], wherein the base steel sheet further contains, as the chemical composition, one or more groups selected from the following groups E to H, in mass %: Group E Ta: 0.10% or less (excluding 0%) F group Te: 0.10% or less (excluding 0%) As: 0.10% or less (excluding 0%) Hf: 0.10% or less (excluding 0%), one or more selected from the following G group Bi: 0.20% or less (excluding 0%) Pb: 0.20% or less (excluding 0%), one or more selected from the following H group Zn: 0.10% or less (excluding 0%) Ge: 0.10% or less (excluding 0%) Sr: 0.10% or less (excluding 0%) Cs: 0.10% or less (excluding 0%), one or more selected from the following [4] The hot-dip galvanized steel sheet according to any one of [1] to [3], wherein the steel structure in the range of 1 / 8 thickness to 3 / 8 thickness centered at the 1 / 4 thickness position from the surface of the base steel sheet has a total area ratio, in area %, of martensite, bainite and retained austenite of 30% or more, and has a tensile strength of 780 MPa or more. [5] The hot-dip galvanized steel sheet according to any one of [1] to [3], wherein the steel structure in the range of 1 / 8 thickness to 3 / 8 thickness centered at the 1 / 4 thickness position from the surface of the base steel sheet has a total area ratio, in area %, of martensite, bainite and retained austenite of 50% or more, and a tensile strength of 980 MPa or more. [6] The hot-dip galvanized steel sheet according to any one of [1] to [3], wherein the steel structure in the range of 1 / 8 thickness to 3 / 8 thickness centered at the position of 1 / 4 thickness from the surface of the base steel sheet has a total area ratio, in area %, of martensite, bainite and retained austenite of 70% or more, and a tensile strength of 1180 MPa or more. [7] The hot-dip galvanized steel sheet according to any one of [1] to [3], wherein the steel structure in the range of 1 / 8 thickness to 3 / 8 thickness centered at the 1 / 4 thickness position from the surface of the base steel sheet has a total area ratio, in area %, of martensite, bainite and retained austenite of 85% or more, and a tensile strength of 1,310 MPa or more. [8] The hot-dip galvanized steel sheet according to any one of [1] to [3], wherein the steel structure in the range of 1 / 8 thickness to 3 / 8 thickness centered at the 1 / 4 thickness position from the surface of the base steel sheet has a total area ratio, in area %, of martensite, bainite and retained austenite of 90% or more, and a tensile strength of 1470 MPa or more. [9] The hot-dip galvanized steel sheet according to any one of [1] to [8], wherein the zinc-based coating layer is a galvannealed layer.
[10] A method for producing a hot-dip galvanized steel sheet, comprising annealing and hot-dip galvanizing a surface of a base steel sheet having a chemical composition according to any one of [1] to [3], A first annealing process in which the base steel sheet is held at a temperature of 650°C to 950°C for 20 s to 150 s in an atmosphere with a dew point of -55°C to +30°C and a hydrogen concentration of 5.0 vol% to 25 vol%; A second annealing process in which the base steel sheet that has been subjected to the first annealing process is held at a holding temperature of 700°C to 950°C for 30 s to 300 s in an atmosphere with a dew point of -50°C to +30°C and a hydrogen concentration of 0.2 vol% to less than 5.0 vol%; a first cooling step in which the base steel sheet having undergone the second annealing step is cooled from the holding temperature of 700°C or more and 950°C or less in the second annealing step to a steel sheet temperature of 650°C or less at an average cooling rate of 5°C / s or more in an atmosphere having a dew point of -20°C or less and a hydrogen concentration of 0.2% by volume or more and less than 5.0% by volume; a second cooling step in which the base steel sheet that has been subjected to the first cooling step is cooled at an average cooling rate of 10°C / s or more from a steel sheet temperature of 650°C or less at the end of the first cooling step to a steel sheet temperature of 550°C or less in an atmosphere with a dew point of -20°C or less and a hydrogen concentration of 5.0 volume% to 25 volume%; a hot-dip galvanizing process for performing a hot-dip galvanizing treatment on the base steel sheet after the second cooling process to form a zinc-based plating layer on a surface of the base steel sheet; A method for producing a hot-dip galvanized steel sheet, comprising:
[11] A method for producing a hot-dip galvanized steel sheet according to
[10] , comprising an oxidation treatment step of subjecting the base steel sheet prior to the first annealing step to an oxidation treatment at a temperature of 400°C or higher and 900°C or lower in an atmosphere containing 1000 ppm by volume or more of O2.
[12] A method for producing a hot-dip galvanized steel sheet according to
[10] or
[11] , comprising a reheating treatment step of holding the steel sheet at a temperature of 200°C or higher and 450°C or lower for a time of 5 s or more and 600 s or less in an atmosphere with a hydrogen concentration of 15 vol% or less, and then cooling the steel sheet.
[13] The method for producing a hot-dip galvanized steel sheet according to any one of [9] to
[12] , further comprising, after the hot-dip galvanizing step, an alloying treatment step of alloying the base steel sheet and the zinc-based plating layer. Effect of the Invention
[0012] According to the present invention, there are provided a hot-dip galvanized steel sheet having high strength, a beautiful surface appearance free of uncoated areas, and excellent delayed fracture resistance, and a method for producing the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] As one embodiment of the hot-dip galvanized steel sheet and its manufacturing method of the present invention, the manufacturing method of the hot-dip galvanized steel sheet and the hot-dip galvanized steel sheet will be described below in that order.
[0014] <Method of manufacturing hot-dip galvanized steel sheet> The method for producing a hot-dip galvanized steel sheet of the present invention is a method for producing a hot-dip galvanized steel sheet by performing a hot-dip galvanizing treatment on the surface of a base steel sheet having a specific component composition described later, and includes a first annealing step of holding the base steel sheet at a holding temperature of 650°C to 950°C for a period of 20 s to 150 s in an atmosphere with a dew point of -55°C to +30°C and a hydrogen concentration of 5.0 vol% to 25 vol%, a second annealing step of holding the base steel sheet that has been subjected to the first annealing step at a holding temperature of 700°C to 950°C for a period of 30 s to 300 s in an atmosphere with a dew point of -50°C to +30°C and a hydrogen concentration of 0.2 vol% to less than 5.0 vol%, and a second annealing step of holding the base steel sheet that has been subjected to the second annealing step at a holding temperature of 700°C to 950°C for a period of 30 s to 300 s in an atmosphere with a dew point of -20°C to +30°C and a hydrogen concentration of 0.2 vol% to less than 5.0 vol%, and the first cooling step of cooling the base steel sheet from the final holding temperature of the first cooling step (a holding temperature of 700°C or more and 950°C or less) to a steel sheet temperature of 650°C or less at an average cooling rate of 5°C / s or more in an atmosphere with a hydrogen concentration of 0.2 vol.% or more and less than 5.0 vol.%, a second cooling step of cooling the base steel sheet that has undergone the first cooling step from the final holding temperature of the first cooling step (a steel sheet having a temperature of 650°C or less at the end of cooling) to a steel sheet temperature of 550°C or less at an average cooling rate of 10°C / s or more in an atmosphere with a dew point of -20°C or less and a hydrogen concentration of 5.0 vol.% or more and 25 vol.%, and a hot-dip galvanizing step of performing a hot-dip galvanizing treatment on the base steel sheet after the second cooling step to form a zinc-based plating layer on the surface of the base steel sheet.
[0015] The temperatures specified in the oxidation treatment, annealing, and cooling after annealing described below are all "steel sheet temperatures", more specifically, the surface temperatures of the steel sheet. A non-oxidizing atmosphere described below refers to an atmosphere in which iron does not oxidize, and is an atmosphere in which selective oxidation of easily oxidizable additive elements such as Si and Mn is permitted. A reducing atmosphere refers to an atmosphere in which iron oxide can be reduced to iron.
[0016] The type of hot-dip galvanized steel sheet to which the present invention is applied is not particularly limited as long as it is a plated steel sheet having a plating layer mainly composed of zinc, and includes not only hot-dip galvanized steel sheet (GI), but also steel sheet subjected to alloying treatment after hot-dip galvanizing (GA). The types of hot-dip galvanized steel sheet include hot-dip galvanized steel sheet (GI) and galvannealed steel sheet (GA), as well as hot-dip galvanized steel sheet (GI) and galvannealed steel sheet (GA), hot-dip zinc-aluminum alloy plated steel sheet, hot-dip zinc-aluminum-silicon alloy plated steel sheet, hot-dip zinc-aluminum-magnesium alloy plated steel sheet, and the like, and the detailed plating composition of each is not limited.
[0017] In the following description, the units of "%" for the content of each element in the composition of the steel sheet (also referred to as the base steel sheet or base steel sheet), the content of each element in the composition of the plating bath, and the degree of alloying of the plating layer are all "mass%", and the units of "%" for the hydrogen concentration in the atmosphere during annealing and cooling are all "volume%". Furthermore, "high strength" steel sheet means that the tensile strength TS of the steel sheet measured in accordance with JIS Z2241 (2011) is 780 MPa or more.
[0018] The manufacturing method of the present invention is a method for manufacturing a hot-dip galvanized steel sheet, which comprises annealing a steel sheet, cooling the steel sheet, and then hot-dip galvanizing the steel sheet. The annealing can be performed in a non-oxidizing atmosphere. The annealing process includes a first annealing step and a second annealing step, in which the steel sheet is annealed in a reducing atmosphere with a high hydrogen concentration and a specified dew point to reduce natural iron oxide present in the surface layer of the steel sheet, and in the subsequent second annealing step, the steel sheet is annealed in a non-oxidizing atmosphere with a low hydrogen concentration and a specified dew point to release hydrogen dissolved in the steel sheet. Furthermore, the cooling can be performed in a non-oxidizing atmosphere. The cooling process also includes a first cooling step and a second cooling step. In the first cooling step, the cooling temperature is relatively higher than that of the second cooling step described below, the steel sheet is annealed in an atmosphere with low hydrogen and a predetermined dew point, and hydrogen dissolved in the steel is further released. In the second cooling step, the cooling temperature is relatively lower than that of the first cooling step, the steel sheet is cooled in an atmosphere with high hydrogen and a predetermined dew point, thereby suppressing oxidation of the steel sheet. After being cooled to a predetermined temperature, the steel sheet is immersed in a hot-dip galvanized plating bath and hot-dip galvanized plating is applied. The manufacturing method of the present invention includes a case where alloying treatment is performed after hot-dip galvanized plating to manufacture a galvannealed hot-dip galvanized plated steel sheet. The hot-dip galvanized plated steel sheet (including the galvannealed hot-dip galvanized plated steel sheet) thus obtained can be controlled to have a total hydrogen release of 0.20 mass% or less at 200°C to 350°C as measured by temperature rise analysis, and has a beautiful surface appearance and good delayed fracture resistance.
[0019] Furthermore, by carrying out an oxidation treatment in a predetermined oxidizing atmosphere to generate iron oxide on the surface layer of the steel sheet before annealing, a more beautiful surface appearance can be obtained. Also, by reheating the plated steel sheet in an atmosphere having a predetermined hydrogen concentration, the delayed fracture resistance can be improved to a higher level. The structure and chemical composition of the steel sheet (base steel sheet) that serves as the base material of the hot-dip galvanized steel sheet will be described in detail later. In the present invention, the oxidation treatment and the subsequent annealing in a non-oxidizing atmosphere are usually performed in a continuous annealing furnace having, in order from the inlet side, an oxidation zone (zone for the oxidation treatment), a reduction zone (zone for the first annealing step), a soaking zone (zone for the second annealing step), a cooling zone 1 (zone for the first cooling step), and a cooling zone 2 (zone for the second cooling step). Here, the oxidation treatment is not an essential step and can be carried out appropriately as necessary.
[0020] The manufacturing method of the present invention will be described below in the order of oxidation treatment, annealing (first annealing step, second annealing step), cooling (first cooling step, second cooling step), hot-dip galvanizing, and reheating.
[0021] Oxidation treatment process In the oxidation treatment, the steel sheet temperature is controlled to 400°C or more and 900°C or less in an atmosphere containing 1000 volume ppm or more of O2, thereby forming iron oxide on the surface layer of the steel sheet (base steel sheet). The atmosphere for the oxidation treatment may contain one or more of N2, CO, CO2, H2O, and NOx in addition to O2. N2 can be contained as an inert gas, CO as a gas for adjusting oxidation and reduction, CO2 as an inert gas, and H2O as a gas for adjusting oxidation and reduction. CO, CO2, H2O, and NOx can also be contained as fuel gas, gas derived from the components of the steel sheet to be annealed, impurity gas in the air, or fuel combustion gas.
[0022] In the present invention, the steel sheet is oxidized by this oxidation treatment, and then reduced in the subsequent annealing (first annealing step) to form a reduced iron layer on the surface layer of the steel sheet, thereby preventing Si and Mn from diffusing into the surface layer of the steel sheet and oxidizing, thereby further improving the galvanizability. In the present invention, in which a low hydrogen atmosphere is used in the second annealing step, both excellent surface quality and excellent delayed fracture resistance are highly improved and achieved. Furthermore, the improvement effect is particularly remarkable in steels containing 0.1% or more Si and 1.5% or more Mn. The oxidation of steel sheet is promoted by setting the O2 concentration in the atmosphere in which the oxidation treatment is performed to 1000 ppm by volume or more. If the O2 concentration is less than 1000 ppm by volume, the oxidation of the steel sheet is insufficient, and oxides of Si and Mn are formed, which may result in a decrease in galvanic properties. The upper limit of the O2 concentration is not particularly limited, but in order to avoid problems such as pick-up onto the transport roll due to peroxidation, it is preferably 50,000 ppm by volume or less, and more preferably 10,000 ppm by volume or less. The atmosphere for the oxidation treatment may contain N2, CO, CO2, H2O, NOx, etc. depending on the gas used, and the ratio of these gases is not particularly limited. Although a more beautiful surface appearance can be obtained by the oxidation treatment, this step is not essential because it is possible to obtain a hot-dip galvanized steel sheet with excellent delayed fracture resistance without the oxidation treatment.
[0023] In the oxidation treatment, the oxidation of the steel sheet is promoted by setting the steel sheet temperature to 400° C. or higher. If the steel sheet temperature is less than 400° C., the amount of oxidation becomes insufficient, and oxides of Si and Mn are formed, which may reduce the effect of improving the plateability. On the other hand, if the steel sheet temperature exceeds 900°C, the amount of oxidation of the steel sheet becomes excessive, and reduction is not completed in the subsequent reduction annealing (first annealing step), and the remaining iron oxide may impair the galvanizing property. For this reason, the oxidation treatment is preferably performed at 400°C or more and 900°C or less. Here, performing the oxidation treatment at 400°C or more and 900°C or less means that the oxidation treatment temperature is at least in the range of 400 to 900°C and does not exceed 900°C. That is, in the present invention, as long as the oxidation treatment is performed at a temperature of 400°C or more and 900°C or less in an atmosphere containing 1000 volume ppm or more of O2, the oxidation treatment may also be performed at a temperature below 400°C (for example, when the oxidation treatment is performed during the temperature rise process from 300°C to 700°C). The oxidation treatment is preferably carried out for a treatment time in the range of 1 to 30 seconds. That is, from the viewpoint of securing a sufficient amount of oxidation and improving plating properties, the treatment time is preferably 1 second or more, more preferably 2 seconds or more, and even more preferably 3 seconds or more. On the other hand, from the viewpoint of preventing excessive oxidation and suppressing pick-up, the treatment time is preferably 30 seconds or less, more preferably 20 seconds or less, and even more preferably 15 seconds or less.
[0024] This oxidation treatment process can also include a process of heating the steel sheet (base steel sheet) to a temperature for annealing. For example, a soaking chamber capable of controlling the atmosphere is provided during the process of heating the steel sheet, and the steel sheet surface can be oxidized by maintaining a constant temperature in a predetermined atmosphere. It is also possible to oxidize the steel sheet surface by controlling the atmosphere in a direct-fire heating furnace equipped with a direct-fire burner while heating the steel sheet. By simultaneously performing heating and oxidation treatment, the furnace can be made compact and the production speed can be improved, which is an industrial advantage. When the surface of the steel sheet is oxidized while heating it, a sufficient amount of oxidation can be obtained by providing an oxidizing atmosphere over a heating range (temperature range) of 50°C or more after the steel sheet temperature reaches 400°C. If the heating range in which the steel sheet is exposed to the oxidizing atmosphere is less than 50°C, the amount of oxidation becomes insufficient, and oxides of Si and Mn are formed, which may reduce the effect of improving the plating property. When the surface of a steel sheet is oxidized while the temperature is being increased, the rate of temperature increase within the oxidation temperature range is preferably set to 3 to 25° C. / s from the viewpoint of ensuring an appropriate amount of oxidation.
[0025] Here, the direct flame burner for the oxidation treatment can be a burner that heats the steel plate by directly applying the burner flame, which is a mixture of fuel such as coke oven gas (COG), a by-product gas from steel mills, and air, to the surface of the steel plate. Heating with such a direct flame burner has the advantage that the furnace length can be shortened and the steel plate conveying speed can be increased because the temperature of the steel plate is increased faster than by radiation heating means. Furthermore, when the air ratio of the direct flame burner is set to 0.95 or more and the ratio of air to fuel is increased, unburned oxygen remains in the flame, and the oxygen can promote the oxidation of the steel plate. Therefore, by adjusting the air ratio, it is possible to control the oxygen concentration in the atmosphere. In addition to COG, liquefied natural gas (LNG), ammonia gas, hydrogen gas, etc. can be used as fuel for the direct flame burner.
[0026] First annealing process In the first annealing process, the steel sheet (base steel sheet) is held at a temperature of 650°C to 950°C for 20 s to 150 s in an atmosphere with a dew point of -55°C to +30°C and a hydrogen concentration of 5.0% to 25%, in which iron oxide is reduced. In the first annealing step, natural iron oxide present on the surface layer of the steel sheet is reduced in a reducing atmosphere to ensure galvanizability. Since the reduction hardly progresses in the subsequent second annealing step in a low hydrogen concentration atmosphere, it is preferable to complete the reduction of iron oxide in this first annealing step. This first annealing step is an essential step for obtaining a good plating appearance. Furthermore, when oxidation treatment is performed, the intentionally formed iron oxide is reduced in a reducing atmosphere in the first annealing step of this reduction annealing to form a reduced iron layer on the steel sheet surface layer, thereby preventing Si and Mn from diffusing into the steel sheet surface layer and being oxidized, and making the appearance even more beautiful. Similarly, even when oxidation treatment is performed, reduction hardly progresses in the subsequent second annealing step in a low hydrogen concentration atmosphere, so it is preferable to reduce the iron oxide in this first annealing step.
[0027] If the annealing temperature of the steel sheet in the first annealing step is less than 650°C, reduction will be insufficient, and iron oxide will become roll pick-up, causing defects in the steel sheet. In addition, in the subsequent second annealing step, the iron oxide will not be substantially reduced, causing bare spots. On the other hand, if the annealing temperature of the steel sheet exceeds 950°C, the life of the furnace body is significantly reduced. For this reason, the annealing temperature of the steel sheet is set to 650°C or higher and 950°C or lower. When the base steel sheet is a cold-rolled steel sheet, the annealing temperature is preferably set to 750°C or higher from the viewpoint of ensuring a predetermined strength and ductility by recrystallization. In order to obtain a high-strength steel sheet having a tensile strength of 780 MPa or more, it is necessary to ensure a predetermined total area ratio of martensite, bainite and retained γ (retained austenite), and the annealing temperature is preferably 780° C. or more. Increasing the annealing temperature in the first annealing step promotes selective oxidation of Si and Mn and increases the amount of hydrogen in the steel. In the present invention, by controlling the atmosphere and holding time in the first annealing step and the second annealing step, the effects of promoting selective oxidation and increasing the amount of hydrogen in the steel can be reduced, and therefore excellent surface quality and excellent resistance to delayed fracture can be provided. To lower the dew point of the atmosphere in the first annealing process below -55°C requires special equipment, which increases costs, but at +30°C or less, the iron oxide in the steel sheet surface layer can be reduced, and the selective oxidation of Si and Mn can be suppressed within the specified annealing time range. If the dew point exceeds +30°C, the dew point distribution in the furnace becomes large, making dew point control difficult and raising concerns about the impact on the furnace body. For this reason, the dew point is set to be between -55°C and +30°C. The dew point is preferably -50°C or higher, and more preferably -45°C or higher. The dew point is preferably 15° C. or less, and more preferably 5° C. or less.
[0028] In the first annealing step, the higher the hydrogen concentration, the faster the reduction of iron oxide is completed and the selective oxidation of Si and Mn is suppressed, but the higher the hydrogen concentration, the easier it is for hydrogen to dissolve in the steel, and the delayed fracture resistance property decreases. In this regard, if the hydrogen concentration is less than 5.0%, the reduction is insufficient. On the other hand, if the hydrogen concentration exceeds 25%, the effect of the reduction is saturated and a large amount of hydrogen is dissolved in the steel, making it difficult to sufficiently reduce the amount of hydrogen in the steel in the subsequent second annealing step. For this reason, the hydrogen concentration in the first annealing step is set to 5.0% or more and 25% or less. In addition, when an oxidation treatment is performed, the hydrogen concentration is preferably 8.0% or more in order to perform sufficient reduction. On the other hand, from the viewpoint of production cost and reduction of hydrogen in the steel, the hydrogen concentration is preferably 22% or less, and more preferably 18% or less.
[0029] If the holding time in the first annealing step is less than 20 seconds at 650°C or more and 950°C or less, the reduction is not fully completed. On the other hand, if the holding time exceeds 150 seconds, the area ratio of martensite and bainite required to obtain a high-strength steel sheet with a tensile strength of 780 MPa or more may not be sufficiently secured. In addition, since the reduction is fully completed with a holding time of 150 seconds or less, if the holding time exceeds 150 seconds, the productivity is unnecessarily reduced. In addition, selective oxidation of Si and Mn progresses, and the surface quality and plating adhesion deteriorate. The amount of hydrogen in the steel is saturated with a holding time of about 20 seconds, and the effect of the holding time is not large. For this reason, the holding time in the first annealing step at 650°C or more and 950°C or less is set to 20 seconds or more and 150 seconds or less. The retention time is preferably 30 seconds or more, and more preferably 40 seconds or more. The retention time is preferably 130 seconds or less, and more preferably 90 seconds or less.
[0030] Second annealing process In the second annealing step of annealing, the steel sheet (base steel sheet) that has been through the first annealing step is held in an atmosphere with a dew point of -50°C or higher and +30°C or lower and a hydrogen concentration of 0.2% or higher and less than 5.0%, at a holding temperature of 700°C or higher and 950°C or lower, for 30 s or higher and 300 s or lower. In this second annealing step, the steel sheet that has been reduced in the first annealing step is maintained in a low hydrogen atmosphere, thereby releasing hydrogen from the steel sheet. If the annealing temperature (holding temperature, soaking temperature) of the steel sheet in the second annealing step is less than 700°C, dehydrogenation is not promoted. On the other hand, if the annealing temperature exceeds 950°C, the furnace body is significantly affected. For this reason, the annealing temperature of the steel sheet is set to 700°C or higher and 950°C or lower. From the viewpoint of reducing the amount of hydrogen in the steel, the annealing temperature in the second annealing step is preferably set to 860°C or lower, and more preferably to 830°C or lower. In order to obtain a high-strength steel sheet having a tensile strength of 780 MPa or higher, it is necessary to ensure a predetermined total area ratio of martensite, bainite, and residual γ, and therefore the annealing temperature in the second annealing step is preferably set to 780°C or higher.
[0031] In the second annealing process, the lower the dew point, the smaller the impact on the furnace body, but to make the dew point less than -50°C, special equipment is required to control the dew point, which increases costs. On the other hand, if the dew point exceeds +30°C, the reduced Fe formed in the first annealing process may be reoxidized and impair the plating properties, and it is also difficult to control the dew point, which raises concerns about the impact on the furnace body. For this reason, the dew point is set to be -50°C or higher and +30°C or lower. From the viewpoint of controllability, the dew point is preferably +20°C or lower, and more preferably +10°C or lower. The dew point is preferably -45°C or higher, and more preferably -40°C or higher. In the second annealing step, the lower the hydrogen concentration, the more hydrogen dissolved in the steel sheet in the first annealing step is released. However, it is difficult to uniformly control the hydrogen concentration in the furnace to less than 0.2%, and there is a concern that the steel sheet may be reoxidized in areas with low hydrogen concentration, so the hydrogen concentration is set to 0.2% or more. On the other hand, if the hydrogen concentration is 5.0% or more, the amount of hydrogen in the steel cannot be sufficiently reduced, so the hydrogen concentration is set to less than 5.0%. From the above viewpoints, the hydrogen concentration is preferably 1.0% or more, and more preferably 2.0% or more. Similarly, the hydrogen concentration is more preferably 4.0% or less.
[0032] If the holding time at 700°C to 950°C in the second annealing step is less than 30 s, hydrogen release is not completed sufficiently. On the other hand, hydrogen release is completed sufficiently with a holding time of 300 s or less, so if the holding time exceeds 300 s, productivity is reduced. In addition, selective oxidation of Si and Mn progresses, deteriorating surface quality and plating adhesion. For this reason, the holding time at 700°C to 950°C in the second annealing step is set to 30 s to 300 s. From the viewpoint of sufficiently releasing hydrogen from the steel, it is preferable that the holding time at 700°C to 950°C in the second annealing step is set to 50 s or more. The retention time is preferably 250 seconds or less, and more preferably 200 seconds or less. In the present invention, a high concentration of hydrogen is required to reduce the iron oxide naturally present on the steel sheet surface or the iron oxide produced by the oxidation treatment in the first annealing step of annealing. Since a large amount of hydrogen is dissolved in the steel accordingly, the balance between reduction and dehydrogenation is important, and therefore the conditions for the first annealing step and the second annealing step in which annealing is performed must be optimized as described above.
[0033] Although the method for changing the hydrogen concentration in the first annealing step and the second annealing step is not particularly specified, it is possible to easily control the atmospheres in the first annealing step and the second annealing step individually by dividing the furnace into two furnaces, using furnaces connected via seal rolls, and controlling the hydrogen concentration and dew point of the gas fed into each furnace. In the present invention, it is preferable to anneal the steel sheet using a continuous annealing furnace capable of controlling two or more separate different atmospheres.
[0034] ·First cooling process The steel sheet (base steel sheet) that has completed annealing (second annealing process) is cooled at an average cooling rate of 5°C / s or more in an atmosphere with a dew point of -20°C or less and a hydrogen concentration of 0.2% or more and less than 5.0%, in the temperature range from the holding temperature at the end of the second annealing process, i.e., the final holding temperature of the second annealing process (holding temperature of 700°C or more and 950°C or less) to a steel sheet temperature of 650°C or less. By cooling at an average cooling rate of 5°C / s or more in the temperature range from the final holding temperature in the second annealing step to a steel sheet temperature of 650°C or less, the desired steel sheet strength can be obtained, and the intrusion of hydrogen in the atmosphere into the steel sheet during cooling can be suppressed, while at the same time, the relatively stable quasi-diffusible hydrogen that was not fully released in the first annealing step can be released. If the average cooling rate is less than 5°C / s, the steel sheet strength is likely to decrease. For this reason, the average cooling rate is set to 5°C / s or more. The average cooling rate is preferably 8°C / s or more. Since special equipment is required to achieve a high cooling rate, the average cooling rate is preferably 40° C. / s or less, and more preferably 30° C. / s or less. The above steel sheet temperature (cooling end temperature of the first cooling step) is preferably 600° C. or higher. If the above steel sheet temperature is less than 600° C., the hydrogen reduction effect is saturated and it becomes difficult to increase the cooling rate, which may make it difficult to ensure the desired microstructure and strength. Furthermore, when the hydrogen content in the atmosphere exceeds 5.0%, relatively stable quasi-diffusible hydrogen is likely to remain in the steel sheet. Here, the final holding temperature in the second annealing step refers to the temperature at which the steel sheet annealed within ranges satisfying the requirements of the annealing temperature, hydrogen concentration, dew point, and holding time in the above-mentioned second annealing step falls outside at least one of the above requirements. The above average cooling rate (°C / s) is obtained by dividing the difference between the cooling start temperature of the first cooling step, i.e., the final holding temperature (°C) of the second annealing step, and the cooling end temperature (650°C or less) of the first cooling step, by the cooling time (s). The cooling end temperature (steel plate temperature of 650°C or less) refers to the temperature at which the hydrogen concentration transitions from less than 5.0% to 5.0% or more.
[0035] The atmosphere of the cooling zone in the first cooling step will be described. Hydrogen has a high cooling ability, so the higher the hydrogen concentration in the atmosphere, the higher the cooling rate can be. However, if the hydrogen concentration is too high, hydrogen may penetrate into the steel sheet during cooling, and the release of quasi-diffusible hydrogen, which is released at 200°C or more and 350°C or less during heating analysis, may be insufficient. When cooling from a relatively high temperature, the cooling efficiency is high, so in the region of 650°C or more, the amount of hydrogen required to obtain a cooling rate of 5°C / s or more is less than that required for cooling at a low temperature. In addition, in the region of 650°C or more, the cooling rate required to obtain the required strength is smaller than the cooling rate below 650°C, which has the greatest effect on the strength of the steel sheet. Therefore, the hydrogen concentration is set to 0.2% or more and less than 5.0%. If the hydrogen concentration is less than 0.2%, there is a risk that a sufficient cooling rate cannot be ensured, and the strength of the steel sheet is likely to decrease. On the other hand, if the hydrogen concentration is 5.0% or more, the cooling rate will be faster, but hydrogen may penetrate into the steel sheet during cooling, and the relatively stable semi-diffusible hydrogen that was not released in the first annealing step will not be released sufficiently. The hydrogen concentration is preferably 0.5% or more, and more preferably 1.0% or more. In addition, the hydrogen concentration is preferably 4.0% or less, and more preferably 3.0% or less. In addition, by setting the dew point to -20°C or lower, it is possible to suppress the reoxidation of the steel sheet at low temperatures, which would cause the galvanization to deteriorate. In other words, if the dew point exceeds -20°C, the steel sheet is likely to reoxidize at low temperatures, which would cause the galvanization to deteriorate. Therefore, the dew point in the first cooling step is set to -20°C or lower. Although there is no particular lower limit, a temperature lower than -55°C requires special equipment for lowering the dew point, which increases costs. Therefore, the dew point in the first cooling step is preferably -55°C or higher.
[0036] ·Second cooling process The steel sheet (base steel sheet) that has completed the first cooling step is cooled from a steel sheet temperature of 650°C or less at the end of the first cooling step (cooling end temperature (650°C or less)) to a steel sheet temperature of 550°C or less at an average cooling rate of 10°C / s or more in an atmosphere with a dew point of -20°C or less and a hydrogen concentration of 5.0% to 25%. It can also be further cooled to a temperature of 150°C to 550°C. Thereafter, after heating as necessary, it is immersed in a hot-dip galvanized plating bath to perform hot-dip galvanized plating. By cooling at an average cooling rate of 10°C / s or more in the temperature range from the end temperature of cooling in the first cooling step to a steel sheet temperature of 550°C or less, the desired steel sheet strength can be obtained and hydrogen in the atmosphere can be prevented from penetrating into the steel sheet during cooling. In the range below 650°C, the cooling rate has a large effect on the strength of the steel sheet, so if the average cooling rate is less than 10°C / s, the strength of the steel sheet is likely to decrease and hydrogen in the atmosphere is likely to penetrate into the steel sheet, resulting in a decrease in delayed fracture resistance. Therefore, the average cooling rate is set to 10°C / s or more. The average cooling rate is preferably 13°C / s or more. Since special equipment is required to achieve a high cooling rate, the average cooling rate is preferably 40° C. / s or less, and more preferably 30° C. / s or less. Here, the cooling end temperature in the first cooling step refers to the temperature at which a steel sheet that has been annealed within ranges satisfying the requirements of the steel sheet temperature, hydrogen concentration, dew point, and holding time in the first cooling step falls outside at least one of the requirements. In addition, the above average cooling rate (°C / s) is obtained by dividing the difference between the cooling start temperature of the second cooling step (the cooling end temperature in the first cooling step) (°C) and the cooling end temperature of the second cooling step (550°C or less) by the cooling time (s).
[0037] In the second cooling step, the temperature during cooling is lower than that in the first cooling step, so even if a higher concentration of hydrogen is present in the atmosphere than in the first cooling step, hydrogen is less likely to penetrate into the steel sheet and is less likely to become relatively stable quasi-diffusible hydrogen. On the other hand, in the second cooling step in the low temperature range, the effect of a decrease in the cooling rate is greater than that in the first cooling step. Therefore, the hydrogen concentration in the atmosphere in the cooling zone is set to 5.0% or more and 25% or less. If the hydrogen concentration is less than 5.0%, there is a risk that a sufficient cooling rate cannot be ensured, and the strength of the steel sheet is likely to decrease. On the other hand, if the hydrogen concentration exceeds 25%, the cooling effect is saturated, hydrogen is likely to penetrate into the steel sheet during cooling, and the relatively stable quasi-diffusible hydrogen also increases, and the delayed fracture resistance property is likely to decrease. The hydrogen concentration is preferably 8.0% or more, and more preferably 10% or more. In addition, the hydrogen concentration is preferably 20% or less, and more preferably 15% or less. In addition, by setting the dew point to -20°C or lower, it is possible to suppress the reoxidation of the steel sheet at low temperatures, which would result in a decrease in galvanization. In other words, if the dew point exceeds -20°C, the steel sheet is likely to be reoxidized at low temperatures, which would result in a decrease in galvanization. Therefore, the dew point in the second cooling step is set to -20°C or lower. Although there is no particular lower limit, a temperature lower than -55°C requires special equipment for lowering the dew point, which increases costs. Therefore, the dew point in the second cooling step is preferably -55°C or higher.
[0038] Hot-dip galvanizing process The conditions of the hot dip galvanizing treatment are not particularly limited, and may be general conditions. That is, preferably, the base steel sheet is cooled in the second cooling step under the above-mentioned conditions, and then the base steel sheet, which is heated to the temperature of the coating bath as necessary, is immersed in the hot dip galvanizing bath to be coated. In the case of GA or GI, the coating bath is composed of Zn, Al, and unavoidable impurities, and the components are not particularly specified, but the Al concentration in the bath is preferably 0.05% or more and 0.250% or less. If the Al concentration in the bath is less than 0.05%, the occurrence of bottom dross increases, and the dross easily adheres to the steel sheet and becomes a defect. On the other hand, if the Al concentration exceeds 0.190%, the top dross increases, and the dross also easily adheres to the steel sheet and becomes a defect, and the addition of Al leads to an increase in cost. In addition, the hot dip galvanizing bath temperature is preferably 440 to 500°C.
[0039] · Alloying process In addition, after the above-mentioned hot-dip galvanizing treatment in the hot-dip galvanizing step, the alloying treatment can be performed subsequently, and the conditions of the alloying treatment when the alloying treatment is performed are not particularly limited. As the conditions of the alloying treatment, it is preferable to perform the alloying treatment by heating the steel sheet having the zinc-based plating layer (hot-dip galvanized steel sheet) to an alloying temperature of 430 ° C or more after the above-mentioned hot-dip galvanizing treatment. The above-mentioned alloying temperature is preferably 600 ° C or less. If the alloying temperature is less than 430 ° C, the Fe-Zn alloying speed is slow, and alloying may be difficult. On the other hand, if the alloying temperature exceeds 600 ° C, Fe-Zn alloying becomes excessive, and in addition to the deterioration of the plating appearance and plating adhesion, untransformed austenite may transform into pearlite, making it impossible to obtain the desired tensile strength. The alloying temperature is more preferably 450 ° C or more. The alloying temperature is more preferably 570 ° C or less.
[0040] Reheating process The steel sheet (hot-dip galvanized steel sheet) that has been subjected to treatment in a hot-dip galvanizing process or further treatment in an alloying process and, if necessary, cooled may be further subjected to temper rolling and heat treatment if necessary, and then reheated under the following conditions: an atmosphere with a hydrogen concentration of 15 volume% or less, a reheating temperature of 200°C or more and 450°C or less, and a reheating time of 5 s or more and 600 s or less. From the viewpoint of promoting the release of diffusible hydrogen in steel during reheating, it is advantageous to lower the hydrogen concentration in the atmosphere. Therefore, the hydrogen concentration is preferably 15% or less, and more preferably 5% or less. The lower limit of the hydrogen concentration is not particularly limited. However, hydrogen is unavoidably contained in the air. Therefore, the hydrogen concentration may be, for example, 0.00001% by volume or more. The remaining gas other than hydrogen (H2) in the atmosphere during reheating is not particularly limited. As an example, the remaining gas may be N2, O2, H2O, CO 2、 Ar and unavoidable impurities, and combinations thereof. The ratio of these is not particularly limited. This reheating may be performed in the air. In order to obtain a sufficient effect of reducing quasi-diffusible hydrogen among hydrogen in steel, the reheating temperature is preferably 200°C or higher. On the other hand, if the reheating temperature exceeds 450°C, the plating layer may remelt, leading to deterioration of the appearance. Therefore, the reheating temperature is preferably 200°C or higher and 450°C or lower. Moreover, the reheating temperature is more preferably 250°C or higher. The reheating temperature is more preferably 400°C or lower. Here, the reheating temperature is the maximum temperature reached during reheating. Moreover, during the holding of reheating, the temperature may be constant or may vary as long as it is within the range of 200°C or higher and 450°C or lower. If the reheating time is less than 5 seconds, the effect of reducing the hydrogen concentration in the steel may not be sufficient. Therefore, the reheating time is preferably 5 seconds or more. The reheating time is more preferably 10 seconds or more, and further preferably 30 seconds or more. On the other hand, from the viewpoint of productivity, the reheating time is preferably 600 seconds or less. The reheating time is a holding time in a temperature range of 200°C to 450°C, which is equal to or higher than the cooling stop temperature after the hot dip galvanizing treatment or further after the alloying treatment.
[0041] In addition, after reheating under the conditions of an atmosphere with a hydrogen concentration of 15 volume % or less, a reheating temperature of 200°C or more and 450°C or less, and a reheating time of 5 s or more and 600 s or less, the hot-dip galvanized steel sheet can be cooled. The above-mentioned temper rolling may be carried out before and / or after the reheating treatment. When temper rolling is carried out, it may be carried out either before or after the reheating treatment step, or both, but it is preferable to set the elongation rate to 0.05% or more and 1.0% or less.
[0042] The conditions other than those mentioned above are not particularly limited, and may be those according to conventional methods.
[0043] <Hot-dip galvanized steel sheet> Next, the high-strength hot-dip galvanized steel sheet will be described. The hot-dip galvanized steel sheet of the present invention comprises a base steel sheet having a composition containing, by mass%, C: 0.06% or more and 0.30% or less, Si: 0.01% or more and less than 3.00%, Mn: 1.5% or more and 3.5% or less, P: 0.1% or less (not including 0%), S: 0.003% or less (not including 0%), sol.Al: 0.1% or less (not including 0%), N: 0.007% or less (not including 0%), O: 0.003% or less (not including 0%), with the balance being Fe and unavoidable impurities; and a coating weight of 20 g / m per side formed on the surface of the base steel sheet. 2 More than 120g / m 2 and a zinc-based plating layer having a thickness of 0.15 to 1.0 mm, and wherein the base steel sheet has a total hydrogen release of 0.20 mass ppm or less at 200°C or higher and 350°C or lower when measured by heating analysis, has less than 3 unplated defects within an area of 1 m x 1 m on the steel sheet surface, and has a tensile strength of 780 MPa or more.
[0044] The coating weight of the zinc-based coating layer on the base steel sheet by hot-dip galvanizing is 20g / m 2 More than 120g / m 2 The coating weight of the zinc-based coating layer on one side may be 20 g / m or less. 2If the thickness is less than 120g / m2, not only is the corrosion resistance likely to decrease, but it is also difficult to control the coating weight. 2 If the coating thickness exceeds 20g / m2, the coating adhesion is likely to decrease. Therefore, the zinc-based coating layer formed on the surface of the base steel sheet should be 20g / m2 or less per side. 2 More than 120g / m 2 It is preferable that: There are no particular limitations on the method for adjusting the coating weight of the zinc-based coating layer, but gas wiping is generally used and adjustment is made by the gas pressure of the gas wiping, the distance between the wiping nozzle and the steel sheet, etc. When alloying treatment is performed after hot dip galvanizing treatment, the degree of alloying of the zinc-based plating layer after alloying treatment is not particularly limited, but the degree of alloying is preferably 7 to 15%. If the degree of alloying is less than 7%, the η phase remains and press formability is likely to decrease, while if it exceeds 15%, plating adhesion is likely to decrease.
[0045] The base steel sheet may be either a cold-rolled steel sheet or a hot-rolled steel sheet. In addition, delayed fracture resistance is a problematic property in high-strength steel sheets, and the steel sheet is preferably a high-strength steel sheet having a tensile strength TS of 780 MPa or more, preferably 980 MPa or more, more preferably 1180 MPa or more, even more preferably 1310 MPa or more, and even more preferably 1470 MPa or more.
[0046] The total amount of hydrogen (quasi-diffusible hydrogen) released at 200°C or more and 350°C or less in the case of measuring by temperature rise analysis contained in the base steel sheet must be 0.20 mass ppm or less. This is because, when measured by temperature rise analysis, diffusible hydrogen released at less than 200°C is released into the atmosphere and rendered harmless to delayed fracture resistance by leaving the high-strength hot-dip galvanized steel sheet for about two weeks after production, whereas the value of quasi-diffusible hydrogen released at 200°C or more and 350°C or less measured immediately after production is hardly reduced by leaving the sheet at room temperature, and thus has a large effect on delayed fracture resistance. The lower the value of this quasi-diffusible hydrogen, the better, and it is preferably 0.15 mass ppm or less, and more preferably 0.10 mass ppm or less.
[0047] Furthermore, the hot-dip galvanized steel sheet of the present invention has less than three uncoated defects in an area of 1 m × 1 m on the steel sheet surface, and has a beautiful surface appearance free of uncoated defects. Uncoated defects can also be evaluated by visually observing the coating appearance of the hot-dip galvanized steel sheet, and the detailed method is as described in the examples below.
[0048] The thickness of the steel plate is not particularly limited, but is preferably 0.5 mm or more, and is preferably 3.2 mm or less.
[0049] ·Ingredient composition A preferred composition of the base steel sheet will now be described. The base steel sheet targeted in the present invention contains, as a chemical composition, C: 0.06% or more and 0.30% or less, Si: 0.01% or more and less than 3.00%, Mn: 1.5% or more and 3.5% or less, P: 0.1% or less (excluding 0%), S: 0.003% or less (excluding 0%), sol.Al: 0.1% or less (excluding 0%), N: 0.007% or less (excluding 0%), O: 0.003% or less (excluding 0%), and further contains one or more elements selected from the following groups A, B, C, D, E, F, G, and H. The reasons for containing each of the above elements are as follows. Group A One or more selected from the following: Nb: 0.05% or less (excluding 0%), Ti: 0.08% or less (excluding 0%), V: 0.2% or less (excluding 0%), W: 0.15% or less (excluding 0%), Zr: 0.15% or less (excluding 0%) Group B One or more selected from the following: Cr: 1% or less (excluding 0%), Ni: 1% or less (excluding 0%), Cu: 1% or less (excluding 0%), Mo: 1% or less (excluding 0%), Co: 1% or less (excluding 0%), B: 0.005% or less (excluding 0%) Group C One or more selected from the following: Ca: 0.005% or less (excluding 0%), Mg: 0.005% or less (excluding 0%), REM: 0.005% or less (excluding 0%) Group D One or more selected from the following: Sn: 0.2% or less (excluding 0%), Sb: 0.2% or less (excluding 0%) Group E Ta: 0.10% or less (excluding 0%) F group One or more selected from the following: Te: 0.10% or less (excluding 0%), As: 0.10% or less (excluding 0%), Hf: 0.10% or less (excluding 0%) G group One or more selected from the following: Bi: 0.20% or less (excluding 0%), Pb: 0.20% or less (excluding 0%) H group One or more selected from the following: Zn: 0.10% or less (excluding 0%), Ge: 0.10% or less (excluding 0%), Sr: 0.10% or less (excluding 0%), Cs: 0.10% or less (excluding 0%)
[0050] ·C: 0.06% or more and 0.30% or less C has the effect of improving workability by forming martensite or the like as a steel structure, but in order to obtain good weldability, the C content is preferably 0.30% or less, more preferably 0.25% or less, while in order to obtain good workability, the C content is 0.06% or more, preferably 0.09% or more.
[0051] Si: 0.01% or more and less than 3.00% Silicon is an effective element for achieving high strength in steel plates because it has a large effect of increasing the strength of steel through solid solution (solid solution strengthening ability) without significantly impairing workability. On the other hand, silicon is also an element that adversely affects the resistance weld cracking resistance characteristics of welded parts. In order to achieve high strength in steel plates, the silicon content is set to 0.01% or more. On the other hand, if the Si content is 3.00% or more, the hot rolling property and cold rolling property are significantly deteriorated, which may adversely affect the productivity and may cause a decrease in the ductility of the steel sheet itself. For this reason, the Si content is set to less than 3.00%. From the above viewpoint, the Si content is preferably 2.50% or less, and more preferably 2.00% or less.
[0052] ·Mn: 1.5% or more and 3.5% or less Mn is an element that strengthens steel by solid solution strengthening, improves hardenability, and promotes the formation of residual γ, bainite, and martensite. These effects are achieved by including 1.5% or more of Mn. For this reason, the Mn content is set to 1.5% or more, and preferably 1.8% or more. On the other hand, if the Mn content is 3.5% or less, the above effects can be obtained without increasing the cost, and therefore the Mn content is set to 3.5% or less, and preferably 3.3% or less.
[0053] P: 0.1% or less (excluding 0%) By suppressing the P content, it is possible to prevent a decrease in weldability, and further to prevent P from segregating to grain boundaries, thereby preventing deterioration of ductility, bendability, and toughness. Furthermore, if a large amount of P is contained, the crystal grain size also becomes large by promoting ferrite transformation. For this reason, the P content is set to 0.1% or less. There is no particular lower limit for the P content, but due to production technology constraints, it is preferable that the P content be 0.001% or more.
[0054] S: 0.003% or less (excluding 0%) It is preferable to reduce the S content as much as possible. By suppressing the S content, it is possible to prevent a decrease in weldability, prevent a decrease in ductility during hot rolling, suppress hot cracking, and significantly improve surface properties. Furthermore, by suppressing the S content, it is possible to prevent a decrease in delayed fracture resistance, ductility, bendability, and stretch flangeability of the steel sheet due to the formation of coarse sulfides as an impurity element. Since the problems caused by S become significant when the S content exceeds 0.003%, the S content is set to 0.003% or less, and preferably 0.002% or less. From the viewpoint of improving delayed fracture resistance, it is preferable to set the S content to 0.001% or less, and more preferably 0.0003% or less. Although there is no particular lower limit for the S content, the S content is preferably 0.0001% or more due to restrictions on production technology.
[0055] Sol.Al: 0.1% or less (excluding 0%) If the sol.Al content exceeds 0.1%, the cost increases, so the sol.Al content is set to 0.1% or less. On the other hand, the lower limit of the sol.Al content is not particularly limited, but since removing Al at the impurity level also leads to increased costs, it is preferable that the sol.Al content be 0.001% or less. Furthermore, since Al is thermodynamically very susceptible to oxidation, it oxidizes prior to Si and Mn, and has the effect of suppressing the oxidation of Si and Mn at the outermost layer of the steel sheet and promoting the oxidation of Si and Mn inside the steel sheet. This effect can be obtained when the sol.Al content is 0.01% or more. Therefore, it is preferable that the sol.Al content be 0.01% or more.
[0056] N: 0.007% or less (excluding 0%) By making the N content 0.007% or less, N forms coarse nitrides with Ti, Nb, and V at high temperatures. This prevents the effect of increasing the strength of the steel plate by adding Ti, Nb, and V from being impaired. In addition, by making the N content 0.007% or less, it is possible to prevent a decrease in toughness. Furthermore, by making the N content 0.007% or less, it is possible to prevent the occurrence of slab cracks and surface defects during hot rolling. For this reason, the N content is made 0.007% or less, preferably 0.005% or less, more preferably 0.003% or less, and even more preferably 0.002% or less. The lower limit of the N content is not particularly limited, but it is preferably 0.0005% or more due to constraints on production technology.
[0057] O: 0.003% or less (excluding 0%) O is an element that forms oxide-based inclusions such as Al2O3, SiO2, CaO, MgO, (Al,Ca)-O, and (Si,Mn)-O in steel, and the generation of these inclusions deteriorates the delayed fracture resistance. In order to reduce such adverse effects on the delayed fracture resistance, the O content is set to 0.003% or less. From the viewpoint of improving the delayed fracture resistance, the O content is more preferably set to less than 0.0030%. The lower limit of the O content is not particularly limited, but in consideration of the industrially feasible lower limit, the O content is preferably set to 0.0005% or more.
[0058] Group A [one or more elements selected from Nb: 0.05% or less (excluding 0%), Ti: 0.08% or less (excluding 0%), V: 0.2% or less (excluding 0%), W: 0.15% or less (excluding 0%), and Zr: 0.15% or less (excluding 0%)] Nb, Ti, V, W, and Zr are all effective elements for increasing the strength of the base steel plate and can be added as necessary. Of these elements in group A, Nb is an element that can obtain a fine structure even with a small amount of Nb, and can increase strength without impairing toughness.
[0059] Nb: 0.05% or less (excluding 0%) The effect of improving strength can be obtained by including 0.005% or more of Nb. However, from the viewpoint of preventing an increase in costs, if Nb is included, the Nb content is set to 0.05% or less.
[0060] Ti: 0.08% or less (excluding 0%) Ti is an element effective for precipitation strengthening of steel. Although there is no particular lower limit for Ti, it is preferable to set it to 0.005% or more in order to obtain the effect of adjusting the strength. However, if Ti is added excessively, the hard phase becomes excessively large and the formability decreases, so when Ti is contained, the Ti content is preferably set to 0.08% or less, and is set to 0.05% or less.
[0061] V: 0.2% or less (excluding 0%) The V content of 0.005% or more has the effect of improving strength, but from the viewpoint of preventing an increase in costs, if V is contained, the V content is set to 0.2% or less.
[0062] W: 0.15% or less (excluding 0%) The effect of improving strength can be obtained by including 0.005% or more of W. However, from the viewpoint of preventing an increase in costs, if W is included, the W content is set to 0.15% or less.
[0063] Zr: 0.15% or less (excluding 0%) The effect of improving strength can be obtained by including 0.0005% or more of Zr, but from the viewpoint of preventing an increase in costs, if Zr is included, the Zr content is set to 0.15% or less.
[0064] B group [one or more elements selected from Cr: 1% or less (excluding 0%), Ni: 1% or less (excluding 0%), Cu: 1% or less (excluding 0%), Mo: 1% or less (excluding 0%), Co: 1% or less (excluding 0%), and B: 0.005% or less (excluding 0%)] Cr, Ni, Cu, Mo, Co, and B are all elements that improve the hardenability of steel sheet.
[0065] Cr: 1% or less (excluding 0%) When Cr is contained in an amount of 0.005% or more, the hardenability is improved and the balance between strength and ductility can be improved. However, from the viewpoint of preventing an increase in costs, if Cr is contained, the Cr content is set to 1% or less.
[0066] Ni: 1% or less (excluding 0%) A Ni content of 0.005% or more can promote the formation of a residual γ phase, but from the viewpoint of preventing an increase in costs, if Ni is contained, the Ni content is set to 1% or less.
[0067] Cu: 1% or less (excluding 0%) Although the Cu content of 0.005% or more can promote the formation of the residual γ phase, from the viewpoint of preventing an increase in costs, when Cu is contained, the Cu content is set to 1% or less.
[0068] Mo: 1% or less (excluding 0%) When Mo is contained in an amount of 0.005% or more, the strength adjusting effect is obtained, and this effect is particularly enhanced when the Mo content is 0.05% or more. However, from the viewpoint of preventing an increase in costs, when Mo is contained, the Mo content is set to 1% or less.
[0069] Cobalt: 1% or less (excluding 0%) Co content of 0.001% or more improves the ultimate deformability of the steel sheet, and improves the stretch flangeability. In particular, the effect is enhanced when the Co content is 0.005% or more. However, from the viewpoint of preventing an increase in costs, when Co is contained, the Co content is set to 1% or less.
[0070] B: 0.005% or less (excluding 0%) B is an element effective in improving the hardenability of steel. In order to improve the hardenability, the B content is preferably 0.0003% or more, and more preferably 0.0005% or more. However, if B is contained excessively, the formability decreases, so if B is contained, the B content is set to 0.005% or less.
[0071] C group [one or more elements selected from Ca: 0.005% or less (excluding 0%), Mg: 0.005% or less (excluding 0%), and REM: 0.005% or less (excluding 0%)] Ca, Mg, and REM (rare earth elements) are all elements used to control the morphology of sulfides.
[0072] Ca: 0.005% or less (excluding 0%) When Ca is contained in an amount of 0.0005% or more, the morphology of sulfides can be controlled and ductility and toughness can be improved. From the viewpoint of obtaining good ductility, however, when Ca is contained, the Ca content is set to 0.005% or less.
[0073] Magnesium: 0.005% or less (excluding 0%) When Mg is contained in an amount of 0.0005% or more, the morphology of sulfides can be controlled and ductility and toughness can be improved. However, from the viewpoint of preventing an increase in costs, if Mg is contained, the Mg content is set to 0.005% or less.
[0074] REM: 0.005% or less (not including 0%) When REM is contained in an amount of 0.0005% or more, the morphology of sulfides can be controlled and ductility and toughness can be improved. From the viewpoint of obtaining good toughness, however, when REM is contained, the REM content is set to 0.005% or less. In the present invention, REM refers to scandium (Sc) with atomic number 21, yttrium (Y) with atomic number 39, and lanthanoids from lanthanum (La) with atomic number 57 to lutetium (Lu) with atomic number 71. The REM content in the present invention is the total content of one or more elements selected from the above-mentioned REM. The REM is not particularly limited, but is preferably La and / or Ce.
[0075] D group [one or more elements selected from Sn: 0.2% or less (excluding 0%) and Sb: 0.2% or less (excluding 0%)] Sb and Sn are elements that suppress decarburization, denitrification, deboronization, etc., and are effective in suppressing a decrease in the strength of the steel sheet. Therefore, when Sb and Sn are contained, their respective contents are set to exceed 0%.
[0076] Sn: 0.2% or less (excluding 0%) Sn is an element that is effective in suppressing denitrification, deboronization, etc., and thus suppressing a decrease in the strength of steel. In order to obtain such an effect, the Sn content is preferably 0.002% or more. On the other hand, in order to obtain good impact resistance, when Sn is contained, the Sn content is set to 0.2% or less.
[0077] Sb: 0.2% or less (excluding 0%) Sb can be added from the viewpoint of suppressing nitridation and oxidation of the steel sheet surface, or decarburization of the steel sheet surface in a region of several tens of microns caused by oxidation. Sb suppresses the nitridation and oxidation of the steel sheet surface, thereby preventing a decrease in the amount of martensite formed on the steel sheet surface, and improving the fatigue properties and surface quality of the steel sheet. To obtain such an effect, the Sb content is preferably 0.001% or more. On the other hand, to obtain good toughness, the Sb content is 0.2% or less.
[0078] Group E [Ta: 0.10% or less (excluding 0%)] Ta, like the elements in group A, is an effective element for increasing the strength of the base steel sheet, and can be added as necessary. Although the effect of improving strength can be obtained by adding Ta at 0.005% or more, from the viewpoint of preventing an increase in costs, if Ta is added, the Ta content is set to 0.10% or less.
[0079] F group [one or more elements selected from Te: 0.10% or less (excluding 0%), As: 0.10% or less (excluding 0%), and Hf: 0.10% or less (excluding 0%)] Te, As, and Hf, like the elements of group C, are all elements used to control the morphology of sulfides.
[0080] Te: 0.10% or less (excluding 0%) When Te is contained in an amount of 0.001% or more, the morphology of sulfides can be controlled and ductility and toughness can be improved. However, from the viewpoint of preventing an increase in costs, when Te is contained, the Te content is set to 0.10% or less.
[0081] As: 0.10% or less (excluding 0%) When As is contained in an amount of 0.001% or more, the morphology of sulfides can be controlled and ductility and toughness can be improved. However, from the viewpoint of preventing an increase in costs, if As is contained, the As content is set to 0.10% or less.
[0082] Hf: 0.10% or less (excluding 0%) When Hf is contained at 0.01% or more, the morphology of sulfides can be controlled and ductility and toughness can be improved. However, from the viewpoint of preventing an increase in costs, if Hf is contained, the Hf content is set to 0.10% or less.
[0083] Group G [one or more elements selected from Bi: 0.20% or less (excluding 0%) and Pb: 0.20% or less (excluding 0%)] Both Bi and Pb are elements that suppress grain boundary segregation and improve ductility and toughness. When Bi and Pb are contained, their respective contents must exceed 0%.
[0084] Bi: 0.20% or less (not including 0%) When Bi is contained at 0.001% or more, it is possible to suppress grain boundary segregation and improve ductility and toughness. Bi also has the effect of improving machinability and smoothness of cut end surfaces, and has the effect of improving delayed fracture resistance of cut surfaces. When Bi is contained, the Bi content is set to 0.10% or less from the viewpoint of preventing an increase in costs.
[0085] Pb: 0.20% or less (excluding 0%) The Pb content of 0.001% or more suppresses grain boundary segregation and improves ductility and toughness. Pb also has the effect of improving machinability and smoothness of cut edges, and improves delayed fracture resistance of cut edges. If Pb is contained, the Pb content is set to 0.10% or less to prevent an increase in costs.
[0086] H group [one or more elements selected from Zn: 0.10% or less (excluding 0%), Ge: 0.10% or less (excluding 0%), Sr: 0.10% or less (excluding 0%), Cs: 0.10% or less (excluding 0%)] Zn, Ge, Sr, and Cs are elements that increase strength without significantly affecting mechanical properties or surface quality. When Zn, Ge, Sr, and Cs are contained, their respective contents must exceed 0%.
[0087] Zn: 0.10% or less (excluding 0%) Even if Zn is contained in an amount of 0.001% or more, it does not have a significant effect on mechanical properties or surface quality. From the viewpoint of preventing an increase in costs, if Zn is contained, the Zn content is set to 0.10% or less.
[0088] Ge: 0.10% or less (excluding 0%) Even if Ge is contained at 0.001% or more, it does not have a significant effect on mechanical properties or surface quality. From the viewpoint of preventing an increase in costs, if Ge is contained, the Ge content is set to 0.10% or less.
[0089] Sr: 0.10% or less (excluding 0%) Even if the Sr content is 0.001% or more, it does not have a significant effect on mechanical properties or surface quality. From the viewpoint of preventing an increase in costs, if Sr is contained, the Sr content is set to 0.10% or less.
[0090] Cs: 0.10% or less (excluding 0%) Even if the Cs content is 0.001% or more, it does not have a significant effect on mechanical properties or surface quality. To prevent an increase in costs, if Cs is contained, the Cs content is set to 0.10% or less.
[0091] In the steel sheet (base steel sheet), the balance other than the above-mentioned composition is Fe and unavoidable impurities.
[0092] ·Steel structure There are no particular limitations on the structure of the base steel sheet (underlying steel sheet), but in order to ensure a tensile strength of 780 MPa or more, it is preferable for the steel sheet structure to be as follows (steel structure in the range of 1 / 8 thickness to 3 / 8 thickness, centered on the 1 / 4 thickness position from the surface of the base steel sheet). That is, it is preferable that the total area ratio of martensite, bainite and retained austenite (retained γ) is 30% or more, thereby obtaining a base steel sheet having a tensile strength of 780 MPa or more.
[0093] Furthermore, by making the total area ratio of martensite, bainite and retained γ 50% or more, a base steel plate having a tensile strength of 980 MPa or more can be obtained, and by making the total area ratio of martensite, bainite and retained γ 70% or more, a base steel plate having a tensile strength of 1180 MPa or more can be obtained.
[0094] Furthermore, by setting the total area ratio of martensite, bainite and residual γ to 85% or more, a base steel sheet having a tensile strength of 1310 MPa or more can be obtained, and by setting the total area ratio of martensite, bainite and residual γ to 90% or more, a base steel sheet having a tensile strength of 1470 MPa or more can be obtained. In addition, in steels having a total area ratio of martensite, bainite and residual γ of 50% or more, particularly 90% or more, the hydrogen diffusion rate is significantly reduced and hydrogen tends to remain in the steel, but by adopting the manufacturing method of the present invention described above, it is possible to reduce quasi-diffusible hydrogen in the base steel sheet of the present invention.
[0095] In order to ensure a desired tensile strength TS, from the viewpoint of obtaining the total area ratio of martensite, bainite, and residual γ, it is particularly desirable to appropriately control the C content, Si content, Mn content, and annealing temperature. For example, in order to obtain a total area ratio of martensite, bainite, and residual γ of 90% or more, it is preferable that the C content is 0.17% or more, the Si content is 0.1% or more, the Mn content is 2.3% or more, and the annealing temperature (particularly the annealing temperature (holding temperature) in the second annealing step) is 820°C or more.
[0096] Here, the size and abundance of each structure are not particularly limited, but as an embodiment of the present invention, the following sizes and abundances can be exemplified. The aspect ratio is the ratio of the length of the major axis to the minor axis perpendicular to the major axis, the thickness is the length of the minor axis, and the circle equivalent diameter is the diameter when the area of each structure is taken as the area of a circle. Martensite includes both tempered martensite and fresh martensite. Tempered martensite has the effect of improving elongation flangeability, and fresh martensite has the effect of improving ductility.
[0097] Tempered martensite Aspect ratio ≦8, equivalent circle diameter ≦30μm Distribution density of carbides inside the structure: 0.10 to 12 pieces / μm 2 Fresh martensite and residual γ Lumpy: Aspect ratio ≦8, Equivalent circle diameter: 3~30μm Granular: Aspect ratio ≦8, Equivalent circle diameter: 0.40μm or more, less than 3μm Plate or film: aspect ratio over 8, thickness: 0.10 to 8μm Bainite Film or plate: aspect ratio >8, thickness ≤8μm Lumpy: aspect ratio ≦8, equivalent circle diameter ≦30μm Distribution density of carbides inside the structure: 0.10 to 6 particles / μm in all forms 2 ·carbide Granular: Aspect ratio ≦8, Equivalent circle diameter: 0.01μm or more, less than 0.40μm Film-like: aspect ratio greater than 8, equivalent circle diameter: 0.01 μm or more, less than 0.10 μm
[0098] As one embodiment of the hot-dip galvanized steel sheet and the manufacturing method thereof according to the present invention, the manufacturing method of the hot-dip galvanized steel sheet and the hot-dip galvanized steel sheet have been described above. According to the present invention, in a manufacturing method of a hot-dip galvanized steel sheet in which a steel sheet is annealed and cooled, and then hot-dip galvanized, the annealing is performed in a first annealing step with a high hydrogen concentration and a second annealing step with a low hydrogen concentration, and the cooling is performed in a first step with a low hydrogen concentration and a second step with a high hydrogen concentration, each under specific conditions, thereby making it possible to produce a hot-dip galvanized steel sheet having a beautiful surface appearance without bare spots and suppressing the quasi-diffusible hydrogen released at 200°C to 350°C during heating analysis to 0.20 mass ppm or less, and thus exhibiting a higher level of delayed fracture resistance. Also, in the present invention, by performing an oxidation treatment before the annealing, and further performing the annealing under more limited conditions, and by performing a pressure reheating treatment in a specific atmosphere after the plating, it is possible to produce a hot-dip galvanized steel sheet having an even higher level of plating appearance and delayed fracture resistance. EXAMPLES
[0099] A slab obtained by melting steel having the chemical composition shown in Table 1 was hot-rolled, pickled, and cold-rolled to form a cold-rolled steel sheet having a thickness of 1.2 mm. This cold-rolled steel sheet was used as the base steel sheet for the hot-dip galvanized steel sheet.
[0100] [Table 1]
[0101] In a continuous hot-dip galvanizing line (CGL) equipped with an all-radiant tube (ART) type annealing furnace, the steel sheets are annealed under the conditions shown in Tables 2 (Table 2-1, Table 2-2), 3, and 5, and then hot-dip galvanized (coating composition: Zn-0.2 mass% Al) and gas wiped to a coating weight of 30 to 70 g / m per side. 2 Then, except for No. 95, the steels were subjected to an alloying treatment. Table 3 also shows examples in which reheating was performed after plating and alloying. Separately from the above-mentioned examples, in a CGL having a direct-fire annealing furnace (DFF-type annealing furnace) with a direct flame burner, a steel sheet was oxidized and annealed under the conditions shown in Table 4, and then hot-dip galvanized (coating composition: Zn-0.2 mass% Al) was applied, and the coating weight per side was adjusted to 30 to 70 g / m by gas wiping. 2 Then, the alloying treatment was carried out. No. 125 (Table 4) is an example in which oxidation treatment was performed at a constant temperature, and the retention time (treatment time) of the oxidation treatment was 8 seconds. In the examples other than No. 125 in Table 4 (Nos. 123, 124, 126 to 148), the oxidation treatment was performed during temperature rise, and the temperature rise rate of the oxidation treatment was in the range of 5 to 20°C / s.
[0102] For the hot-dip galvanized steel sheets thus obtained, the amount of diffusible hydrogen in the steel sheets and the evaluation of the coating appearance and delayed fracture resistance were performed using the following measurement and evaluation methods. The results are shown in Tables 2 to 5 together with the manufacturing conditions. Here, in the oxidation treatment of the examples in Table 4, the "oxidation start temperature" is the entry strip temperature of the oxidation zone in the heating zone of a DFF-type annealing furnace, the "oxidation end temperature" is the exit strip temperature of the oxidation zone, and the oxygen concentration is the oxygen concentration in the oxidation zone. Therefore, the range from the oxidation start temperature to the oxidation end temperature is the oxidation treatment temperature. Also, the "oxidation temperature range" is the temperature range over which the steel sheet rises in temperature in the oxidation zone (the temperature range from the oxidation start temperature to the oxidation end temperature), and the "maximum steel sheet temperature" is the maximum temperature reached in the heating zone of a DFF-type annealing furnace. Therefore, when the "maximum steel sheet temperature" is higher than the "oxidation end temperature", the steel sheet is further heated in a non-oxidizing atmosphere in the zone next to the oxidation zone (a zone that is not an oxidation zone), and the maximum temperature reached in the zone next to the oxidation zone is the "maximum steel sheet temperature". The primary cooling end temperature (final holding temperature (steel sheet temperature) in the first cooling step) was 650°C for Nos. 1 to 148, and was changed between 600 and 640°C for Nos. 149 to 151 shown in Table 5.
[0103] [Table 2-1]
[0104] [Table 2-2]
[0105] [Table 3]
[0106] [Table 4]
[0107] [Table 5]
[0108] -Measurement of the amount of quasi-diffusible hydrogen in steel sheets (hydrogen analysis method) A rectangular test piece with a major axis length of 30 mm and a minor axis length of 5 mm was taken from the width center of the hot-dip galvanized steel sheet. The zinc plating layer of the test piece was removed with a router. Immediately, hydrogen analysis was performed using a thermal desorption analyzer under conditions of an analysis start temperature of 25°C, an analysis end temperature of 400°C, and a heating rate of 200°C / hour, and the amount of released hydrogen (mass ppm / min), which is the amount of hydrogen released from the test piece surface at each temperature, was measured. The total amount of hydrogen released from 200°C to 350°C was calculated as the amount of diffusible hydrogen in the steel. Here, the amount of diffusible hydrogen in the steel was rated as excellent (◎+) when it was 0.05 ppm by mass or less, excellent (◎) when it was more than 0.05 ppm by mass and less than 0.10 ppm by mass, good (◯) when it was more than 0.10 ppm by mass and less than 0.15 ppm by mass, and fair (△) when it was more than 0.15 ppm by mass and less than 0.20 ppm by mass. From experience, when the amount of diffusible hydrogen in the steel exceeds 0.20 ppm by mass, the delayed fracture resistance often decreases, so that when it exceeds 0.20 ppm by mass, it was rated as poor (×).
[0109] ·Evaluation of plating appearance The appearance of the plating on hot-dip galvanized steel sheets was visually observed, and those without any patterns or irregularities were rated as excellent "◎". For those with patterns or irregularities, SEM observation of the relevant areas at a magnification of 50x determined that areas not covered by zinc plating over an area of 1.0mm x 1.0mm or more on the steel sheet were uncoated defects, and 3D shape measurement at 10x determined that irregularities over an area of 0.5mm x 0.5mm or more on the steel sheet with a maximum height of 5μm or more compared to the average height of the surrounding area were rated as pressure scratches. More specifically, a non-galvanized defect refers to an area of 1.0 mm x 1.0 mm or more where the zinc plating is not coated and which is observed in a darker contrast than the zinc plating coated area when a backscattered electron image is observed using an SEM at an accelerating voltage of 15 kV and a magnification of 50 times. Even if patterns or unevenness were observed, those without any uncoated defects were rated as good (○+), and those with three or more uncoated defects within a 1m x 1m area on the steel sheet surface were rated as poor (×). Also, those without any uncoated defects but with marks caused by picking up the rolls or a sign of such marks, such as a V-shaped scale pattern in the sheet running direction, or those with less than three uncoated defects within a 1m x 1m area on the steel sheet surface were rated as passing (○), although not good (○+).
[0110] Tensile Test A JIS Z2241 No. 5 test piece was taken from the hot-dip galvanized steel sheet in the direction perpendicular to the rolling direction (so that the sheet width direction was the tensile direction), and a tensile test was performed on this test piece in accordance with JIS Z2241 (2011) to measure the tensile strength (TS).
[0111] Observation and measurement of base steel sheet structure The total area ratio of martensite, bainite and retained austenite (retained γ) in the base steel sheet structure was measured as follows. A sample was cut out so that the cross section (L cross section) parallel to the rolling direction of the steel sheet and parallel to the sheet thickness direction was the observation surface, and the observation surface of this sample was polished with diamond paste, and then finish-polished with alumina. Next, the observation surface of the sample was etched with 3 vol% nital to reveal the structure. The observation position was set to 1 / 4 of the sheet thickness on this sample observation surface, and five fields of view were observed at a magnification of 3000 times using an SEM. It was determined that the steel structure was observed in the range of 1 / 8 to 3 / 8 thickness, centered on the 1 / 4 thickness position from the surface of the base steel sheet. The total area of martensite, bainite and retained γ was calculated from the obtained structural images, and the area ratio was calculated by dividing this total area by the measured area for five fields of view, and the average of these values was taken as the total area ratio of martensite, bainite and retained γ. The discrimination of martensite, bainite, retained γ and other microstructures was performed as follows. Martensite There are two types of martensite: tempered martensite and fresh martensite. Tempered martensite Tempered martensite is a gray or dark gray area close to black in SEM photographs. Tempered martensite has a blocky morphology with boundaries at the interfaces with other structures such as prior gamma grain boundaries and ferrite. However, tempered martensite may contain other structures such as bainite inside and have a concave shape. Tempered martensite contains many carbides inside, but depending on the plane orientation, there may be only a small amount of carbides. Fresh martensite Fresh martensite is the grey or white area in the SEM photograph. Fresh martensite is in the form of blocks, granules, plates, or films and does not contain carbides. Bainite Bainite is the dark gray area in the SEM photograph. Bainite is in the form of a film, a plate, or a mass formed by some or all of these adjacent areas being connected, and contains a small amount of carbides inside. Bainite also includes carbides that have been coarsened by tempering after formation. ·Residual austenite (retained γ) The retained γ is an area that has the same color and morphology as the above-mentioned fresh martensite. Note that the retained γ and fresh martensite cannot be distinguished by SEM.
[0112] In order to ensure the strength of the steel plate, it is necessary to control the total area ratio of the martensite, bainite, and retained γ described above, but the balance may include the structures shown below, but is not limited thereto. Ferrite Ferrite is the black area in the SEM photograph. Ferrite has a blocky morphology and contains almost no carbides. Bainitic ferrite contains almost no carbides inside and has similar mechanical properties to ferrite, so it belongs to the ferrite category. Ferrite may contain either or both granular and blocky fresh martensite, and either or both granular and blocky retained gamma. Fresh martensite and retained gamma contained in ferrite are not included in the area ratio of ferrite, but are treated as the area ratio of fresh martensite or retained gamma. ·carbide Carbides are the white regions in SEM photographs. Carbides are in the form of grains or films. Carbides form finely mainly inside ferrite, martensite, and bainite, but the area ratio of these is small and can be ignored, so the area ratio of carbides is not excluded from the area ratio of each structure, but is included in it. - Organizations other than those mentioned above In addition to the above, nitrides such as TiN, carbonitrides such as (Nb,Ti)(C,N), sulfides such as MnS and CaS, and oxides such as Al2O3 and SiO2 may also be contained at a total area ratio of a few percent. As the area ratios of these are small and can be ignored, these area ratios are included in the area ratios of each structure that contains them. In some cases, pearlite may also be included. In the case of pearlite, the area ratio of pearlite is calculated separately.
[0113] - Evaluation of delayed fracture resistance A rectangular test piece with a major axis length of 100 mm and a minor axis length of 20 mm was taken from the hot-dip galvanized steel sheet in the direction perpendicular to the rolling direction, and a punched hole with a diameter of 15 mm and a clearance of 14.0% was formed at the center of the major and minor axes of the test piece. The clearance was previously set to about 12.5%, but in light of the recent trend toward stricter quality standards for delayed fracture resistance, a more stringent condition was adopted than before. The test piece was subjected to a tensile test, and the delayed fracture resistance was evaluated based on the presence or absence of delayed fracture from the punched hole. In order to prevent the release of diffusible hydrogen in the steel due to changes over time, the time from taking the rectangular test piece from the hot-dip galvanized steel sheet to starting the delayed fracture tensile test (tensile speed 10 mm / min) was set to within 10 minutes. The loading time of the tensile test was set to a maximum of 100 hours, and the maximum stress at which no cracks (here, cracks mean fractures when tensile stress is applied) did not occur after 100 hours of loading was set as the limit stress, and the delayed fracture resistance was evaluated by the ratio of the limit stress to the yield stress. The evaluation criteria for delayed fracture resistance are as follows: when the critical stress / yield stress is 1.10 or more, it is excellent (◎), when it is less than 1.10 and 1.05 or more, it is good (〇), when it is less than 1.05 and 1.00 or more, it is not good (○) but acceptable (△), and when it is less than 1.00, it is poor (×). Note that the delayed fracture resistance evaluated in the delayed fracture test is generally lower (disadvantageous) for steel plates with higher strength.
[0114] According to Tables 1 to 5, the hot-dip galvanized steel sheets of the examples of the present invention have high strength and a beautiful surface appearance without uncoated areas, and also have excellent delayed fracture resistance.
Claims
1. In mass percent, C: 0.06% or more and 0.30% or less, Si: 0.01% or more and less than 3.00%; Mn: 1.5% or more and 3.5% or less, P: 0.1% or less (excluding 0%) S: 0.003% or less (excluding 0%) sol. Al: 0.1% or less (excluding 0%), N: 0.007% or less (excluding 0%) O: Contains 0.003% or less (excluding 0%), A base steel plate having a composition with the balance being Fe and unavoidable impurities; The coating weight per side formed on the surface of the base steel sheet is 20 g / m 2 120g / m or more 2 and a zinc-based plating layer, The base steel sheet has a total hydrogen release amount of 0.20 mass ppm or less at 200° C. or more and 350° C. or less when measured by temperature rise analysis, Within an area of 1 m x 1 m on the steel sheet surface, there are less than three uncoated defects; A hot-dip galvanized steel sheet having a tensile strength of 780 MPa or more.
2. The hot-dip galvanized steel sheet according to claim 1, wherein the base steel sheet further contains, as the component composition, one or more elements selected from the following groups A to H, in mass %: Group A Nb: 0.05% or less (excluding 0%) Ti: 0.08% or less (excluding 0%) V: 0.2% or less (excluding 0%) W: 0.15% or less (excluding 0%) Zr: 0.15% or less (excluding 0%), one or more selected from the following: Group B Cr: 1% or less (excluding 0%) Ni: 1% or less (excluding 0%) Cu: 1% or less (excluding 0%) Mo: 1% or less (excluding 0%) Co: 1% or less (excluding 0%) B: 0.005% or less (excluding 0%), one or more selected from the following Group C Ca: 0.005% or less (excluding 0%) Mg: 0.005% or less (excluding 0%) REM: 0.005% or less (excluding 0%), one or more selected from the following Group D Sn: 0.2% or less (excluding 0%) Sb: 0.2% or less (excluding 0%), one or more selected from the following: Group E Ta: 0.10% or less (excluding 0%) F group Te: 0.10% or less (excluding 0%) As: 0.10% or less (excluding 0%) Hf: 0.10% or less (excluding 0%), one or more selected from the following G group Bi: 0.20% or less (excluding 0%) Pb: 0.20% or less (excluding 0%), one or more selected from the following H group Zn: 0.10% or less (excluding 0%) Ge: 0.10% or less (excluding 0%) Sr: 0.10% or less (excluding 0%) Cs: 0.10% or less (excluding 0%), one or more selected from the following
3. 3. The hot-dip galvanized steel sheet according to claim 1, wherein a steel structure in a range of ⅛ thickness to ⅜ thickness centered at a position of ¼ thickness from a surface of the base steel sheet has a total area ratio, in area %, of martensite, bainite and retained austenite of 30% or more, and a tensile strength of 780 MPa or more.
4. 3. The hot-dip galvanized steel sheet according to claim 1, wherein a steel structure in a range of ⅛ thickness to ⅜ thickness centered at a position of ¼ thickness from a surface of the base steel sheet has a total area ratio, in area %, of martensite, bainite and retained austenite of 50% or more and a tensile strength of 980 MPa or more.
5. 3. The hot-dip galvanized steel sheet according to claim 1, wherein a steel structure in a range of ⅛ thickness to ⅜ thickness centered at a position of ¼ thickness from a surface of the base steel sheet has a total area ratio, in area %, of martensite, bainite and retained austenite of 70% or more, and a tensile strength of 1180 MPa or more.
6. 3. The hot-dip galvanized steel sheet according to claim 1, wherein a steel structure in a range of ⅛ thickness to ⅜ thickness centered at a position of ¼ thickness from a surface of the base steel sheet has a total area ratio, in area %, of martensite, bainite and retained austenite of 85% or more and a tensile strength of 1310 MPa or more.
7. 3. The hot-dip galvanized steel sheet according to claim 1, wherein a steel structure in a range of ⅛ thickness to ⅜ thickness centered at a position of ¼ thickness from a surface of the base steel sheet has a total area ratio, in area %, of martensite, bainite and retained austenite of 90% or more, and a tensile strength of 1470 MPa or more.
8. The hot-dip galvanized steel sheet according to claim 1 or 2, wherein the zinc-based plating layer is a galvannealed layer.
9. A method for producing a hot-dip galvanized steel sheet by subjecting a surface of a base steel sheet having the component composition according to claim 1 or 2 to annealing and hot-dip galvanizing treatment, A first annealing process in which the base steel sheet is held at a holding temperature of 650°C to 950°C for 20s to 150s in an atmosphere with a dew point of -55°C to +30°C and a hydrogen concentration of 5.0% by volume to 25% by volume; A second annealing step in which the base steel sheet subjected to the first annealing step is held at a holding temperature of 700°C to 950°C for 30 s to 300 s in an atmosphere with a dew point of -50°C to +30°C and a hydrogen concentration of 0.2 vol% to less than 5.0 vol%; A first cooling process in which the base steel sheet subjected to the second annealing process is cooled from the holding temperature of 700°C or more and 950°C or less in the second annealing process to a steel sheet temperature of 650°C or less at an average cooling rate of 5°C / s or more in an atmosphere having a dew point of -20°C or less and a hydrogen concentration of 0.2% by volume or more and less than 5.0% by volume; a second cooling step in which the base steel sheet having undergone the first cooling step is cooled at an average cooling rate of 10°C / s or more in an atmosphere having a dew point of -20°C or less and a hydrogen concentration of 5.0 volume% or more and 25 volume% or less from a steel sheet temperature of 650°C or less at the end of the first cooling step to a steel sheet temperature of 550°C or less; a hot-dip galvanizing process for performing a hot-dip galvanizing treatment on the base steel sheet after the second cooling process to form a zinc-based plating layer on a surface of the base steel sheet; Including, a zinc-based plating layer formed on a surface of the base steel sheet and having a plating coating weight per side of 20 g / m2 or more and 120 g / m2 or less, wherein the base steel sheet has a total hydrogen release of 0.20 mass ppm or less at 200°C or more and 350°C or less when measured by temperature rise analysis, has less than 3 unplated defects within an area of 1 m x 1 m on the steel sheet surface, and has a tensile strength of 780 MPa or more.
10. The base steel sheet before the first annealing process is 2 The method for producing a hot-dip galvanized steel sheet according to claim 9, further comprising an oxidation treatment step of performing an oxidation treatment at a temperature of 400° C. or higher and 900° C. or lower in an atmosphere containing 1000 ppm by volume or more of
11. 10. The method for producing a hot-dip galvanized steel sheet according to claim 9, further comprising a reheating treatment step of holding the steel sheet at a temperature of 200° C. or higher and 450° C. or lower for a time of 5 s to 600 s inclusive in an atmosphere having a hydrogen concentration of 15 vol% or lower, and then cooling the steel sheet.
12. The method for producing a hot-dip galvanized steel sheet according to claim 10, further comprising a reheating treatment step of holding the steel sheet at a temperature of 200° C. or higher and 450° C. or lower for a time of 5 s to 600 s inclusive in an atmosphere having a hydrogen concentration of 15 vol% or lower, and then cooling the steel sheet.
13. The method for producing a hot-dip galvanized steel sheet according to claim 9, further comprising, after the hot-dip galvanizing step, an alloying treatment step of alloying the base steel sheet and the zinc-based plating layer.
14. The method for producing a hot-dip galvanized steel sheet according to claim 10, further comprising, after the hot-dip galvanizing step, an alloying treatment step of alloying the base steel sheet and the zinc-based plating layer.
15. The method for producing a hot-dip galvanized steel sheet according to claim 11, further comprising, after the hot-dip galvanizing step, an alloying treatment step of alloying the base steel sheet and the zinc-based plating layer.
16. The method for producing a hot-dip galvanized steel sheet according to claim 12, further comprising, after the hot-dip galvanizing step, an alloying treatment step of alloying the base steel sheet and the zinc-based plating layer.
Citation Information
Patent Citations
Replacement cycle notification method of bidet nozzle
KR1020230172265A
Hot stamp molded product and steel sheet for hot stamping
WO2021106936A1
Steel sheet and manufacturing method therefor
WO2021251276A1
Hot-dip galvanized steel sheet and method for producing same, and member
WO2022270053A1
Manufacture of zinc plated steel sheet
JP1979130443A